Enforcing human rights : towards an egalitarian Sri Lanka - Hoole, S. Ratnajeevan H.; International Centre for Ethnic Studies (Colombo : International Centre for Ethnic Studies, 2003)
Contributed articles presented earlier at two seminars.
Keywords: United Nations. -- Commission on Human Rights -- Congresses; Human rights -- Sri Lanka -- Congresses; Whistle blowing -- Sri Lanka -- Congresses; Administrative law -- Sri Lanka -- Congresses